Polysilazane‐Coated Films Achieving Record‐High Moisture Barrier Performance with Sub‐10 Seconds Densification Using High‐Power VUV Irradiation - Luyang Song; He Sun; Yoshiyuki Suzuri (Advanced Science)
Abstract An ultra‐high moisture barrier compact SiNX film can be achieved from solution‐processed perhydropolysilazane (PHPS) through vacuum ultraviolet (VUV) light exposure. This study investigates the photochemical reactions and photo‐densification of PHPS‐based barrier films under varying VUV light intensities, focusing on their effects on barrier performance. Photo‐dehydrogenation of PHPS, involving N─H and Si─H bond cleavage, is efficient and unaffected by light intensity. However, photo‐densification shows a strong dependence on light intensity, particularly above 290 mW cm−2. Higher intensities enhance Si─N bond cleavage, alter film dynamics, and reduce free volume through bond rearrangement, facilitating rapid network reconstruction essential for ultra‐high barrier properties. High‐power VUV light at 309 mW cm−2 establishes a new benchmark for ultra‐high barrier films via solution processing, achieving a record‐low average water vapor transmission rate (WVTR) of 1.6 × 10−5 g m−2 day−1. Films are produced in under 10 s per layer, maintaining a barrier property of 3.8 × 10−5 g m−2 day−1. The optimal refractive index for the top 30 nm layer is 1.74–1.77, controlling WVTR within 10−5 g m−2 day−1, ensuring superior barrier performance for flexible electronic devices, such as perovskite solar cells and organic photovoltaics.